Absorción de exponente 15 N de los fertilizantes en una rotación Allium sativum - Setaria italica, en lisímetros - Lazzari, M.A; Rosell, R.A; Landriscini, M.R. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
Nitrogen uptake by an annual rotation of garlic (Allium sativum/ and millet Setaria italica) from tagged urea and ammonium sulfate applied toa Typic Haplus toll in a battery of differential weighing lysimeters was studied during three years. The °N fertilizers were only applied to the garlic and the nitrogen recovery was determined in leaves, fnuits (bulbs in garlic and seeds in millet), and roots of both Crops Each year total (added plus residual) tagged nitrogen was applied at a rate of ca. 20 g/m. The N recovery in the garlic crop was about 30% with a dry bulb yield of ca. 700 8/n* for both nitrogen treatments. The H uptake in the millet was approximately 15% and the grain yield oscillated between 1616 and i105 g/m* with urea and between 1384 and 1236 g/m* with ammonium sulfate during the three years of the experiment.